Completion Phenomenon in Transcortical Sensory Aphasia - Y. Nakagawa; H. Tanabe; M. Ikeda; H. Kazui; K. Ito; N. Inoue; Y. Hatakenaka; T. Sawada; H. Ikeda; J. Shiraishi (Behavioural Neurology)
We investigated completion phenomenon for proverbs in cases demonstrating transcortical sensory aphasia due to a variety of diseases. Lack of this completion was exclusively observed in patients with focal atrophy. These patients showed a selective and consistent impairment in word comprehension without phonemic cue effects in naming. The completion phenomenon was present in patients demonstrating transcortical sensory aphasia due to other cerebral diseases. In these patients, comprehension deficits were not selective for words, or words not comprehended were inconsistent and some phonemic cue effects were observed. In a previous study, we reported that completion phenomena for multiplication tables, serial numbers and names of days were frequently noted in patients with focal atrophy. Together with the present findings, these results suggest that lack of proverb completion may be attributed to a selective, systematic and complete loss of the meaning representations for language units such as words and proverbs. In addition, pathological processes of focal atrophy with temporal predominance might selectively affect the semantic memory for language as a unit.